COMPARISON OF TWO DIFFERENT DOSAGES OF COMBINATION OF INTRAVENOUS GRANISETRON WITH INTRAVENOUS DEXAMETHASONE AS A PROPHYLAXIS FOR NAUSEA AND VOMITING IN CAESAREAN SECTION WITH SUBARACHNOID BLOCK - Sjattar, Irfan Faisal; Gaus, Syafruddin; Salahuddin, Andi; Seweng, Arifin (Jurnal Kesehatan, 2022)
Granisetron can be used to treat and prevent nausea and vomiting in patients receiving chemotherapy or radiotherapy, as well as during or after surgery. To compare the effects of two doses of intravenous granisetron on nausea and vomiting in Caesarean section with subarachnoid block. This study was a randomized double-blind clinical trial. Subjects were randomized into two groups: Granisetron 10 mcg/kg (GD10) and granisetron 25 mcg/kg (GD25). Dexamethasone 0.1 mg/kg was also administered to all subjects. A total of 21 subjects were included for each group. Data was analyzed using Mann Whitney U test. The results When comparing the incidence of nausea and vomiting in the GD10 and GD25 groups, there was a significant difference in the incidence of nausea (p = 0.001). In the GD10 group, there were nine participants who experienced nausea, whereas the GD25 group had none. Neither of the groups experienced vomiting, hence no additional therapy given to both groups. Granisetron is a selective 5-HT3 receptor antagonist and an effective antiemetic during and after neuraxial anesthesia for Caesarean section. The combination of granisetron and dexamethasone has been reported to be more potent than granisetron alone. Administration of granisetron 25 mcg/kg had a positive impact on patients, with no incidence of nausea and vomiting compared to administration of granisetron 10 mcg/kg.